2014
DOI: 10.12968/bjnn.2014.10.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary management of dysphagia following stroke

Abstract: Dysphagia (difficulty swallowing) is common following stroke. It significantly affects quality of life and places patients at risk of pneumonia, malnutrition and death. An interdisciplinary approach is necessary to ensure patients with dysphagia remain safe. This paper provides a review of current practice in the UK and current evidence in the management of dysphagia following stroke. The roles of the dietitian, nurse, pharmacist and speech and language therapist in dysphagia management are discussed. The arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…With pharmacists performing dysphagia screening in the community setting, this could open a referral pathway to the speech pathologist for thorough assessment and advice; and would allow pharmacists to identify and prevent potentially serious medication misadventure. 9 , 10 The value of having pharmacist input to assess patients who are taking medications which increase falls risk, was highlighted by an occupational therapist to tailor their implementation of home safety measures. This would be significant because there are many medications which increase drowsiness, dizziness, decrease bone mineral density and overall falls risk, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With pharmacists performing dysphagia screening in the community setting, this could open a referral pathway to the speech pathologist for thorough assessment and advice; and would allow pharmacists to identify and prevent potentially serious medication misadventure. 9 , 10 The value of having pharmacist input to assess patients who are taking medications which increase falls risk, was highlighted by an occupational therapist to tailor their implementation of home safety measures. This would be significant because there are many medications which increase drowsiness, dizziness, decrease bone mineral density and overall falls risk, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Limited availability of varied dosage forms creates challenges when it comes to clinical decision making, therefore it has been suggested that collaboration between these two disciplines may target early intervention strategies to optimize medication management and prevent worsening conditions. 10 Occupational therapists’ collaboration with pharmacists has the potential to improve home-health care services, evaluate patient medication-related skills and identify risks of non-adherence. 11 This collaboration will allow recommendations for supportive aids to reduce medication misadventure, implementation of health literacy interventions, and additional support for palliative care services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Post-stroke dysphagia (PSD), with 2024 ICD-10-CM Diagnosis Code I69.391 (dysphagia following cerebral infarction), is related to the decline of oral, pharyngeal, and esophageal functioning, in addition to other serious problems, such as airway obstruction, aspiration, aspiration pneumonia, dehydration, malnutrition, sepsis, and death; it can also lead to social isolation, affect the patient quality of life, and may lead to the delay of rehabilitation and increase the economic burden. [ 2 ] Therefore, it is very important to effectively accelerate the recovery of swallowing function to reduce these risks.…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia is a common complication following stroke with reported incidences around 20%-78% however varying greatly in the literature, depending on assessment process (Arnold et al, 2016;Flowers, Silver, Fang, Rochon, & Martino, 2013;Martino, Martin, & Black, 2012, Martino et al, 2005National Stroke Foundation., 2010). The management of poststroke dysphagia is multidisciplinary with nurses playing a key role in screening for dysphagia risk, monitoring tolerance of food and fluids and providing feedback regarding current status to other team members (McFarlane et al, 2014, Hines et al, 2011, Bird, 2001, Cichero et al, 2009, Daniels et al, 2012, Kertscher et al, 2014, Smithard, 2016, Speyer, 2013, Trapl et al, 2007. Despite the efforts of the multidisciplinary team, dysphagia following stroke is often associated with a number of clinical complications including aspiration pneumonia, dehydration, malnutrition and subsequently the need for non-oral feeding (Arnold et al, 2016;Dziewas et al, 2004;Foley, Martin, Salter, & Teasell, 2009).…”
Section: Introductionmentioning
confidence: 99%